Knowledge, Attitudes, and Practices Toward Antibiotic Use in Food-Producing Animals Among University Students in Seven Cities in Southern and Central China: A Cross-Sectional Study - Hui Sun; Jiajia Zhang; Junjie Zhu; Boya Xu; Yinyan Gao; Dexing Zhang; Irene X. Y. Wu; Yanhong Jessika Hu; Shuzhen Deng (Antibiotics)
Background: The misuse of antibiotics in both humans and food-producing animals poses significant risks to human health and contributes to the rise of antibiotic resistance. Raising public awareness is crucial to managing antibiotic resistance, particularly among university students, as they represent a future force in tackling this global issue. Methods: A cross-sectional study was conducted from July 2022 to May 2024 in seven cities in Southern and Central China to assess university students’ knowledge, attitude, and practice regarding antibiotic use in humans and food-producing animals. Binary logistic regression was used to identify associated factors. Results: A total of 6357 students from 72 universities participated. Less than half of the students answered the knowledge items appropriately. Only 21.47% to 29.98% had a proper understanding of basic antibiotic concepts and their use in humans and food-producing animals. Respectively, 21.49% and 28.50% students paid attention to antibiotic content in food from food-producing animals and refused to buy food containing antibiotics. Factors associated with higher knowledge, attitude, and practice total scores included being male, being of older age, having a postgraduate education, majoring in the medical science discipline, studying at a double-first-class university, having a higher family monthly income, having parents in the medical area, and using antibiotics in the past year (p < 0.001). Conclusions: Given students’ insufficient knowledge—particularly in identifying antibiotics and understanding their functions—and inappropriate practices related to purchasing food from food-producing animals, targeted education programs are suggested. These programs should address the fundamental concepts of antibiotic use in both humans and food-producing animals while providing practical guidance on individual behaviors to help mitigate antibiotic resistance.